The evolution of supportive supervision in low- and middle-income countries - Khaled Shorbaji; Gabriel L. Shedul; Nanna Ripiye; Dike Ojji; Lisa R. Hirschhorn; Charles W. Goss; Mark D. Huffman (BMC, 2026)
Abstract Supportive supervision has shifted in low- and middle-income countries (LMICs) from hierarchical, inspection-based oversight toward collaborative, mentorship-driven approaches that emphasize two-way communication, joint problem-solving, and formative feedback. Evidence across diverse LMIC settings shows that supportive supervision can produce measurable improvements in healthcare worker performance, with particularly large gains when supervisors themselves receive coaching and when supervisory encounters prioritize collaborative problem-solving. Innovations such as peer and group supervision, facility-based internal supervision, and digital platforms have expanded the reach and adaptability of supervision systems, although digital tools alone consistently yield modest improvements in provider practices. Broader implementation packages that pair supervision with health-system enablers—such as strengthened infrastructure, supply chains, financing, and management—achieve substantially larger effects than supervision combined with training alone, highlighting the importance of addressing structural barriers to performance. Despite its demonstrated potential, supportive supervision is not a standalone solution; its effectiveness depends on alignment with local context, clear definitions and expectations, adequate resourcing, and integration within broader quality-improvement and systems-strengthening strategies. When selected through structured problem diagnosis and paired with appropriate complementary interventions, supportive supervision offers a pragmatic, scalable approach to improving frontline clinical performance and advancing high-quality, equitable care in LMIC health systems.
Keywords: Supportive supervision; Implementation science; Low- and middle-income countries (LMICs); Healthcare worker performance; Digital tools for supervision; Peer supervision; Health systems strengthening